Physical training prevent and treat hepatic lipid accumulation induced by fructose-rich diet - Gaspar, Rafael Calais; Kuga, Gabriel Keine [UNESP]; Muñoz, Vitor Rosetto; Coope, Andressa; Cambri, Lucieli Teresa; Ghezzi, Ana Carolina; Moura, Leandro Pereira de [UNESP]; Leme, José Alexandre Curiacos de Almeida; Pauli, José Rodrigo; Botezelli, José Diego (PPUFU - Portal de Periódicos da Universidade Federal de Uberlândia, 2018)
This study aims to examine the effects of physical training performed in early (preventive) or late (therapeutic) protocols on body weight gain, glucose tolerance, and triglycerides accumulation in rats fed on a fructose-rich diet. Wistar rats were allocated into two major groups according to the diet received: Control (C-standard diet) and Fructose (F-diet containing 60% fructose) fed during 120 days. Next, these two groups were distributed into six groups: C and F that were kept inactive; CTE (Control Trained Early) and FTE (Fructose Trained Early) that were submitted to Anaerobic Threshold (AnT) training from 28 to 120 days; CTL (Control Trained Late) and FTL (Fructose Trained Late) trained from 90 to 120 days. Physical Training was composed by swimming (5 days/week) at AnT determined by maximum lactate stead state (MLSS). The Oral Glucose Tolerance Test (oGTT) was performed 48h after the last in vivo analysis and did not showed differences between the groups. After, the animals were euthanized for heart, liver, and adipose tissue extraction. The early exercised animals had lower body weight compared to their sedentary littermates. Also, the fructose-rich diet increased liver lipids content in the sedentary animals and physical training successfully reduced this parameter in both major groups. These results suggests that physical training at the AnT performed in early or late protocols are effective to prevent and treat metabolic disorders related to fructose intake.
Treinamento físico previne e trata acumulação lipídica hepática induzida por dieta rica em frutose
Keywords: Adiposity; Hepatic steatosis; Overweight; Physical exercise